The Effect of Attitude and Purchasing of Millennials Consumers Towards Brand Love in Sports Wear Brands - Siti Maemunah ,Puguh Hadi Susanto (International Journal of Advanced Science and Technology, 2020)
The aim of this study is to show that the millennial consumers are looking for well-known brands that have quality in sportswear that meets the millennial needs as a brand love for these products. Millennial attitudes towards sports clothing brands and millennial purchases are affected by several important factors such as brand passion, social media, brand awareness, brand love, brand loyalty, and purchase intention. The methodology in this study is a data collection throughout an online survey of millennial representative groups. Data analysis was performed using SEM (Structural Equation Method) with the AMOS program. The findings in this study found that millennial consumers who have different ages and levels of education have different attitudes towards brand love in sports clothing brands. The implication of this study is that respondents were taken in Indonesia. It is encouraged in the future that the research should consider larger or different areas to get different responses. Furthermore, broader, demographic and cultural variables such as occupation, gender, and marital status can be considered. The practical implication is that the relationship between millennial consumers’ attitudes and purchases can be useful for managers for a better understanding of millennial consumers regarding products in sports apparel brands related to marketing strategies.